A Review on Recent Developments in Transition Metal and Heteroatom‐Doped Carbon Catalysts for Oxygen Reduction Reaction - Khatun A. Jannath; Heru Agung Saputra (Electrochemical Science Advances)
ABSTRACT Oxygen reduction reaction (ORR) is key in many green energy conversion devices like fuel cells and metal‐air batteries. Developing cheap and robust electrocatalysts is crucial to expedite the slow ORR kinetics at the cathode. Lately, transition metal (TM) and heteroatom‐doped carbon catalysts have surfaced as promising cathode materials for ORR as they display admirable electrocatalytic activity and distinguished properties like tunable morphology, structure, composition and porosity. This review summarizes the recent breakthrough in TM (Fe, Co, Mn and Ni) and heteroatoms (N, S, B, P and F) doping in carbon materials. Moreover, their ORR activity and active sites are inspected for future augmentation in making ORR catalysts for electrochemical devices. The existing challenges and prospects in this field are ratiocinated in conclusion.